(untitled) (Bangladesh Medical Journal, 2020)
We face many problems in diagnosis, monitoring and adopting treatment policy.There are very limited studies about preterm labour prevention in our country and few national data are available about the incidence of preterm labour. Acute tocolysis prevents preterm labor for 48 hours, which is the critical period for antenatal steroid administration or maternal transfer to perinatal centers to improve neonatal outcomes. This prospective study was conducted. To determine the effectiveness of magnesium sulfate as tocolytic agent in preterm labour to arrest the premature onset of labour. A total of 90 primigravid and multigravid with preterm labour was included in this study at 250 Beded General Hospital Tangail from January 2012 to December 2015. The mean age of the respondents was 24.13±4.67 year. The mean systolic and diastolic blood pressure were 122.47±12.64 and 71.67±12.67 mm of Hg respectively. Gestational age did not influence on the outcome of treatment with Tocolytic regime. Out of 90 pregnant women, 70% were anemic, 53.3% had vaginal bleeding and 76.7% had abdominal pain. Among 90 respondents only 6 women had premature rupture of membrane and about 40% had inadequate amniotic fluid. The three treatment regime (Antibiotic+ Tocolytic+ steroid) was found indifferent in terms of affectivity. Preterm labour is not a very uncommon pregnancy-related complication. This study evaluates, the effect of magnesium sulphate as tocolytic agent. Bangladesh Med J. 2020 May; 49(2) : 25-29